Analisis Kualitas Jasa Pada Bisnis Perbankan Syariah Berdasarkan Adaptasi Model Carter - soviyanti, efrita (Jurnal Daya Saing, 2016)
Abstract: This research aims knowing how big service quality factors from CARTER model influence customer satisfaction, knowing the rate of customer satisfaction of sharia bank that analyzed with CARTER model, and making improvement priority to enhance service quality for it. To fulfill the aims, it is used factor analysis and path analysis.The result of this research has got several conclusions( 1) Factor analysis showed that factogrouped to 8 factors.The eight factors is influencing customer satisfaction directly as big as 12,01% and indirectly as big as 36%. (2)The rate of customer satisfaction of sharia banking that analyzed by CARTER model adaptation show that 56% respondents told satisfied over ally with sharia banking service in Pekanbaru. (3)Quality improvement can be done for reliability, competence, responsiveness, assurance, emphaty, tangible knowing the customer and compliance. Keywords: Service quality, Customer satisfaction, SERVQUAL, CARTER Model.